EKSPLORASI NIAT PENGGUNAAN E-GOVERNMENT DI KOTA PADANG MELALUI APLIKASI SI RANCAK - Mila Yunita Sari; Vera Pujani; Yulihasri (Halu Oleo University, 2024)
This study aims to analyze the factors that influence the behavioural intention of the people of Padang City to use e-government services known as SI RANCAK. This research uses a quantitative approach using a survey. Data collection on 150 respondents who have KK Padang City and non-users SI RANCAK with purposive sampling method. The data were then analyzed using Structural Equation Modeling - Partial Least Square (SEM-PLS). The results showed that performance expectancy, computer self-efficacy, and trust have a positive and significant effect on attitude. Facilitating conditions are also proven to have a positive and significant effect on effort expectancy. Attitude and trust are also proven to have a positive and significant effect on behavioural intention. Meanwhile, this study found that effort expectancy, social influence, and perceived risk have no significant effect on attitude. Facilitating conditions were also found to have no significant effect on attitude. The implication of this research is that the government is expected to be able to provide supporting facilities and infrastructure so that administrative arrangements can be completed quickly such as providing a helpdesk, improve the security of the SI RANCAK system and provide guarantees to the public that their personal data will not be misused by any party, also provide support in the form of socialization about SI RANCAK both offline and online on social media.